Factors that Influence Student Interest in Choosing a Major in Higher Education - Enjelina Panggoa; Sitihamra; Susi Susantiy; Octamaya Tenri Awaru (Formosa Journal of Applied Sciences, 2023)
Choosing a major in college is a crucial decision for students, which is influenced by internal factors such as interests and talents, as well as external factors such as the social and family environment. This research summarizes the factors that influence students' interest in choosing a major, with a focus on internal and external factors. In the context of this research, the use of the literature study method is used for in-depth analysis of relevant concepts referring to the collection and examination of papers, journals, books and other literature sources related to factors that influence students' interest in choosing a major. Research results suggests that personal interests, social interactions with peers, family support, and available information play key roles in students' decision making.